STRATEGI GURU PAI DALAM MEMBANGUN TOLERANSI DI MAJLIS TA’LIM AL-MUAWWANAH YANG MULTIKULTURAL - Syalwa, Ana Tiara; Musthofa, Taufik (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to describe and analyze the strategies applied by Islamic Religious Education (PAI) teachers in building tolerance attitudes at Majlis Ta'lim Al-Muawwanah which has a multicultural background of students. In the context of a culturally diverse society, ethnicity, and religious understanding, the role of PAI teachers becomes very strategic in instilling tolerance values in order to create social and religious harmony. This research used a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The results showed that PAI teachers at Majlis Ta'lim Al-Muawwanah implemented several strategies, including the integration of tolerance values in teaching materials, dialogical approach in learning, and habituation of mutual respect through religious and social activities. These strategies have proven to be effective in fostering mutual respect between worshipers of different backgrounds. This study concludes that success in building tolerance is highly dependent on PAI teachers' awareness of the importance of inclusive education and a humanist approach in teaching religion.